Caretaker Government Under The Constitution Republic of Iraq For The Year 2005 - Mohammed, QaysJasim; haimus, Mohammed SalimL (International Journal of Psychosocial Rehabilitation, 2020)
The caretaker government, or the so-called caretaker government, is a temporary government for a short period of time and is lacking in authority as it does not possess all the powers that the permanent government possesses according to the electoral merit. Of the issues, whether legislative or administrative, outside the scope of the caretaker government, due to the seriousness and importance of these actions, which made according to the constitutional and legal legislation the competence of the elected and permanent governments. The study dealt with this issue according to a plan that was divided into two requirements. Then we discussed in the second requirement the legislative and legal powers of the caretaker government, and then we turned to the practical reality of the caretaker government in Iraq since the resignation was submitted to the government of Prime Minister Adel Abdul Mahdi, especially since the 2005 constitution of Iraq did not include any text regulating the state of resignation of the Prime Minister.